Directors’ compensation. what really matters? - Acero, Isabel; Alcalde, Nuria (Journal of Business Economics and Management, 2020)
In the current scenario of increasing social inequality, the debate over the compensation received by directors and executives of large listed companies, and its justification, has intensified. Drawing on Agency Theory and Human Capital Theory, a multilevel analytical technique is used in this paper to examine the influence of firm-level variables and director-level variables on the individual compensation of the members of the board. The results obtained for the continental European context (Spain in particular) partially support the Human Capital Theory. Nevertheless, there is no evidence supportive of Agency Theory, as corporate governance mechanisms do not contribute to moderate the compensation of directors and there is no relationship between corporate performance and the compensation of directors. The analyses by subsamples (categories of directors) reveal that non-executive director’s compensation seems to be set for a group of individuals as a whole, depending mainly on firm-level characteristics, whereas executive director compensation is more based on the unique characteristics that a particular executive brings to the board.